Look Who's Talking: Pre-Verbal Infants’ Perception of Face-to-Face and Back-to-Back Social Interactions - Augusti, Else-Marie; Melinder, Annika; Gredebäck, Gustaf (Frontiers in Psychology, 2010)
Four-, 6-, and 11-month old infants were presented with movies in which two adult actors conversed about everyday events, either by facing each other or looking in opposite directions. Infants from 6 months of age made more gaze shifts between the actors, in accordance with the flow of conversation, when the actors were facing each other. A second experiment demonstrated that gaze following alone did not cause this difference. Instead the results are consistent with a social cognitive interpretation, suggesting that infants perceive the difference between face-to-face and back-to-back conversations and that they prefer to attend to a typical pattern of social interaction from 6 months of age.